Analytical and numerical modelling for dual-resonator vibration-based electromagnetic generator - Ooi, B.L. (IEEE Computer Society, 2014)
This paper presents a method which offers the possibility of widening the bandwidth of an electromagnetic energy harvester by utilizing a novel dual-resonator method. The proposed device consists of two separate resonator systems (coil & magnet), which each comply with their respective resonance frequencies, but which, together, give an extended bandwidth. Basic analytical models are derived and a numerical model is implemented in MATLAB-Simulink. The predictive results indicate that for a low damping system, there is a maximum of 75 improvement of the induced voltage within the Intermediate Region which lies between the two resonator frequencies. Nonetheless, the improvement of the induced voltage in the region does come with some sacrificing of the outputs at the side frequencies, which is highly susceptible to the value of the damping factor of the respective resonators. Â© 2014 IEEE.